Antibiotic consumption surveillance in rehabilitation facilities – a new task according to § 23 of the German Infection Protection Act. Data from rehabilitation facilities in the Rhine-Main area, 2016–2018 - Heudorf, Ursel (GMS Hyg Infect Control, 2020)
Background: Multidrug-resistant pathogens are a major health problem in many countries. In Germany, in accordance with the German Antibiotic Resistance Strategy (DART), the surveillance of antibiotic consumption in acute care hospitals and rehabilitation facilities was made mandatory by the Infection Protection Act in 2011 and 2017. Whereas comparable reference data for acute care hospitals are available, such data is lacking for rehabilitation facilities. Therefore, the Rhine-Main network on MDRO (Multi Drug Resistant Organisms) has offered to evaluate the antibiotic consumption of the network's rehabilitation facilities. Antimicrobial consumption (if possible already given as daily defined doses, DDD) and patient days from 2016–2018 were requested. Materials and methods: By October 31, 2019, nine clinics, including a facility for early neurological rehabilitation, reported their consumption of antibiotics (mostly already as DDD) and patient days from 2016–2018. The information from the clinics was entered in an Excel table and the DDD calculated if necessary. In order to compare the facilities, the DDD/100 patient days (pd) were calculated for the individual active substances. Results: Antibiotic consumption in general rehabilitation facilities decreased slightly from 4.8 DDD/100 pd to 4.4 DDD/100 pd from 2016 to 2018. In early neurological rehabilitation, antibiotic consumption increased from 10.2 DDD/100 pd to 13.1 DDD/100 pd in the same period. Among the most commonly used antibiotics, cefuroxime came first, followed by ciprofloxacin and amoxicillin in third place. Discussion: To our knowledge, this is the first antimicrobial consumption data from rehabilitation facilities in Germany. Antibiotic consumption in general rehabilitation facilities is less than 10% of the consumption in normal/regular wards of acute care clinics, and the consumption in neurological early rehabilitation was approximately 10% of the consumption in intensive care wards within acute care clinics. Reserve or broad-spectrum antibiotics were rarely or not used at all in the rehabilitation facilities. Despite this overall positive situation, antibiotic stewardship should also be introduced in rehabilitation facilities, possibly with the support of the regional MDRO networks.